STRATEGI PEMASARAN PRODUK LOKAL DI ERA DIGITAL PADA PENJUALAN UMKM DONAT QU DI JALAN TUASAN - Muhammad Ikhsan Al Rasyid; Muhammad Al fahmi; Minta Ito Lubis; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study examines digital marketing strategies implemented by the Donat Qu MSME in enhancing sales performance in the digital era. The purpose of this research is to analyze the effectiveness of digital marketing practices in supporting business growth across multiple branches. This study employs a qualitative descriptive method using observation, interviews, and documentation as data collection techniques. The research focuses on several Donat Qu branches located in Tuasan, Gaperta, Namira, and Darussalam, including a newly established branch that began operations in May 2025. The findings indicate that the utilization of digital platforms such as social media and online communication channels has contributed positively to increasing brand awareness, expanding market reach, and improving customer engagement. Differences in operational hours across branches also influence marketing effectiveness and consumer purchasing behavior. Overall, digital marketing plays a significant role in strengthening the competitiveness and sustainability of local MSMEs in the digital era.